The black slaves in Peru and Colonial and Republican America: its contribution to the economy and culture - Jaramillo García, Enrique (2017)
In this essay, we reflect on the life and social existence of black African slaves in Peru, and colonial and republican America, and its contribution to strengthening the economy, and the configuration of culture in contemporary society. Moreover, we accredit the critical discussion about the enslavement of black Africans to understand this social phenomenon, as part of a dynamic that began and developed in America / New World in the fifteenth, sixteenth and onwards, within the framework of Western globalization in its most cruel and ruthless oppression and exploitation forms by the action of the colonial aristocracy and the Republican oligarchic plutocracy. We also appreciate the social action developed by the African slaves, to overcome the inhuman and adverse conditions of discrimination and segregation to which they were subjected; and therefore their epic struggle for their freedom and emancipation, in a context of global colonization.